2009
DOI: 10.1038/nnano.2008.418
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-up growth of fully transparent contact layers of indium tin oxide nanowires for light-emitting devices

Abstract: Thin layers of indium tin oxide are widely used as transparent coatings and electrodes in solar energy cells, flat-panel displays, antireflection coatings, radiation protection and lithium-ion battery materials, because they have the characteristics of low resistivity, strong absorption at ultraviolet wavelengths, high transmission in the visible, high reflectivity in the far-infrared and strong attenuation in the microwave region. However, there is often a trade-off between electrical conductivity and transpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
132
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 170 publications
(140 citation statements)
references
References 25 publications
8
132
0
Order By: Relevance
“…[http://dx.doi.org/10.1063/1.4875457] Indium tin oxide (ITO) or Sn doped In 2 O 3 nanowires (NWs) are important as transparent conducting oxides (TCOs) for the fabrication of solar cells, [1][2][3] flexible displays, 4 and ultra violet light emitting diodes [5][6][7][8][9] because it has been suggested that higher Sn doping levels and conductivities can be attained in ITO NWs compared to bulk ITO. So far ITO NWs have been grown by carbothermal reduction of In 2 O 3 and SnO 2 5 but the control of stoichiometry is not trivial as it has been observed that SnO 2 NWs may be obtained even when a higher content of In 2 O 3 is used during carbothermal reduction carried out under an inert gas flow at elevated temperatures 10,11 which also leads to the non-intentional incorporation of carbon.…”
Section: Fermi Level Position © 2014 Author(s) All Article Contentmentioning
confidence: 99%
“…[http://dx.doi.org/10.1063/1.4875457] Indium tin oxide (ITO) or Sn doped In 2 O 3 nanowires (NWs) are important as transparent conducting oxides (TCOs) for the fabrication of solar cells, [1][2][3] flexible displays, 4 and ultra violet light emitting diodes [5][6][7][8][9] because it has been suggested that higher Sn doping levels and conductivities can be attained in ITO NWs compared to bulk ITO. So far ITO NWs have been grown by carbothermal reduction of In 2 O 3 and SnO 2 5 but the control of stoichiometry is not trivial as it has been observed that SnO 2 NWs may be obtained even when a higher content of In 2 O 3 is used during carbothermal reduction carried out under an inert gas flow at elevated temperatures 10,11 which also leads to the non-intentional incorporation of carbon.…”
Section: Fermi Level Position © 2014 Author(s) All Article Contentmentioning
confidence: 99%
“…62 Two-probe transport measurements through the NW layerterminated wafers and the unetched wafers were acquired. Contacts were made by sputtering Al on the back of the Si NW electrodes in situ following Ar þ plasma oxide removal.…”
Section: E Electrical Conductivity Of Rough and Mesoporous Si Nwsmentioning
confidence: 99%
“…The tradeoff between optical and electrical conductiv ity around the plasma frequency has motivated research into controlled and graded porosity in materials and structures to offset transparency loss in conductive oxides [2][3][4][5][6]. Metal oxide TCOs lead to the use of oxide semiconductors in many key optoelectronic devices such as TFTs [7], photovoltaics [8], solar cells [9] and electrochromics [10].…”
Section: Introductionmentioning
confidence: 99%